Indigenous arts in visual arts teaching: a bibliographic review from the production of brazilian postgraduate studies (Palíndromo, 2022)
This article is the result of the research we are developing in the Master's Degree in Visual Arts at UFPB/UFPE and arises from the need to focus on the academic productions of Brazilian postgraduate researchers who investigated indigenous arts in the teaching of Visual Arts in basic education, given the low visibility of these studies. Thus, our objective is to investigate the Brazilian theses and dissertations around the indigenous theme in the teaching of Visual Arts. Methodologically, we opted for a bibliographic review, exploring the database of the Biblioteca Digital Brasileira de Teses e Dissertações (BDTD) of the Instituto Brasileiro de Informação em Ciência e Tecnologia (IBICT) in the time frame from 2010 to 2020, from the following descriptors: Art Education, Visual Arts and Indigenous Arts. The analysis of the content of five dissertations contributed to understanding some gaps, silencing and stereotyping about indigenous arts and makes us reflect on the need to work on this theme in an intercultural and decolonial perspective.
Keywords: Indigenous arts; Art Education; Literature review; Decoloniality; Interculturality